Świętość eremity Piotra Galaty według Teodoreta z Cyru - Budzanowska-Weglenda, Dominika Łucja (Vox Patrum, 2025)
The aim of this article is to explore how Theodoret of Cyrrhus in Historia religiosa portrays Syrian ascetics and their practices leading to sanctity – especially in the biography of Peter of Antioch, known as Peter Galata, to whom the author devoted part of the of the work. The figure of the author is briefly recalled. Above all, the article is an an analysis of excerpts from chapter IX of the Historia religiosa (in Greek and Polish translation), in which Theodoret included a Peter’s biography, his origins, the purpose of his expedition to Palestine, a description of his ascetic lifestyle when he settled in Antioch, the eremite’s benevolent contacts with its inhabitants, including his long-standing relationship with Theodoret’s family, his miracles, his life of the Word of God and prayer. The wider context related to the Church of Syria in the 4th century and the lives of other ascetics there.